In search of the inland Carnian Pluvial Event: Middle–Upper Triassic transition profile and U–Pb isotopic dating in the Yanchang Formation in Ordos Basin, China. (17th December 2019) - Sun, Yuewu; Li, Xiang; Liu, Quanyou; Zhang, Mingda; Li, Peng; Zhang, Rui; Shi, Xiao
Abstract : The Carnian Pluvial Event (CPE) in the early Late Triassic is a global climate change. The CPE is not only recorded in the ocean but also on the continent. It has been well‐documented in the marine environments in Tethys and boreal areas. However, it is less reported for the terrestrial. As a global precipitation event, the CPE on the supercontinent Pangaea is related directly to the sudden increase in argillaceous transportation in the marine carbonate platform. Here, we report a chronological study of the Yunmeng profile in south‐eastern Ordos Basin, China where the continuous lacustrine deposits developed with several tuff interlayers. Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) U–Pb isotopic dating of zircons from three bentonite samples show weighted mean ages of 234.1 ± 2.4 Ma, 234.8 ± 2.1 Ma, and 236.0 ± 1.7 Ma, respectively. Based on the review of isotopic dating, sedimentary and palaeontological characteristics of the Triassic Yanchang Formation, the Middle and Upper Triassic boundary is located at the bottom of Chang 7 oil layer (YC7) in the Yanchang Formation at the Yunmeng profile in the Ordos Basin. Therefore, the Yunmeng profile provides a potential case for understanding the inland CPE and might link the terrestrial and oceanic systems in the Carnian.